2006
DOI: 10.1103/physrevlett.96.176601
|View full text |Cite
|
Sign up to set email alerts
|

Using a Quantum Dot as a High-Frequency Shot Noise Detector

Abstract: We present the experimental realization of a quantum dot (QD) operating as a high-frequency noise detector. Current fluctuations produced in a nearby quantum point contact (QPC) ionize the QD and induce transport through excited states. The resulting transient current through the QD represents our detector signal. We investigate its dependence on the QPC transmission and voltage bias. We observe and explain a quantum threshold feature and a saturation in the detector signal. This experimental and theoretical s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
136
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(141 citation statements)
references
References 16 publications
(26 reference statements)
2
136
3
Order By: Relevance
“…Interactively coupled mesoscopic and nanoscale circuits, such as quantum wires (Debray et al, 2000(Debray et al, , 2001Laroche et al, 2011;Morimoto et al, 2003;Yamamoto et al, 2006), quantum dots (Aguado and Kouwenhoven, 2000;Onac et al, 2006) or point contacts (Khrapai et al, 2006(Khrapai et al, , 2007, provided new fruitful ways of studying Coulomb drag phenomena and revealed a plethora of interesting physics. These devices typically have dimensions smaller than the temperature length L T = v F /T and voltage-related length scale L V = v F /(eV ), and differ substantially from their two-dimensional quantumwell counterparts in several important ways.…”
Section: A Quantum Dots and Quantum Point Contactsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interactively coupled mesoscopic and nanoscale circuits, such as quantum wires (Debray et al, 2000(Debray et al, , 2001Laroche et al, 2011;Morimoto et al, 2003;Yamamoto et al, 2006), quantum dots (Aguado and Kouwenhoven, 2000;Onac et al, 2006) or point contacts (Khrapai et al, 2006(Khrapai et al, , 2007, provided new fruitful ways of studying Coulomb drag phenomena and revealed a plethora of interesting physics. These devices typically have dimensions smaller than the temperature length L T = v F /T and voltage-related length scale L V = v F /(eV ), and differ substantially from their two-dimensional quantumwell counterparts in several important ways.…”
Section: A Quantum Dots and Quantum Point Contactsmentioning
confidence: 99%
“…Twolevel pulse technique was used to detect individual electron spin (Elzerman et al, 2004). Quantum dots were also used as high-frequency noise detectors (Onac et al, 2006). Transport measurements on adjacent but electrically isolated quantum point contacts (QPCs) exhibit a counterflow of electrons [i.e.…”
Section: Coulomb Drag At the Nanoscalementioning
confidence: 99%
“…As one see, the transient current-current correlations have been expressed explicitly in terms of our nonequilibrium Green's functions u(t, t 0 ) and v(τ, t) that determine the dissipation and fluctuation coefficients in the exact master equation (10).…”
Section: Transient Current-current Correlationsmentioning
confidence: 99%
“…[16][17][18][19] The asymmetric noise spectrum, which is directly proportional to the emission-absorption spectrum of the system, 20 has been demonstrated experimentally. [9][10][11][12] In recent years, the higher order current-correlations in a nonequilibrium steady state are also explored both in experimental and theoretical studies. 21,22 The above investigations were focused on the steadystate transport regime.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation